Salivary Cytokines and Airways Disease Severity in Patients with Cystic Fibrosis - Alice Castaldo; Paola Iacotucci; Vincenzo Carnovale; Roberta Cimino; Renato Liguori; Marika Comegna; Valeria Raia; Gaetano Corso; Giuseppe Castaldo; Monica Gelzo (Diagnostics, 2020)
About 50% of patients with cystic fibrosis (CF) have sinonasal complications, which include inferior turbinate hypertrophy (NTH) and/or nasal polyposis (NP), and different degrees of lung disease, which represents the main cause of mortality. Monitoring of sinonasal disease requires complex instrumental procedures, while monitoring of lung inflammation requires invasive collection of bronchoalveolar lavage fluid. The aim of this study was to investigate the associations between salivary cytokines levels and CF-related airway diseases. Salivary biochemical parameters and cytokines, i.e., interleukin-6 (IL-6), IL-8, and tumor necrosis factor alpha (TNF-α), were analyzed in resting saliva from healthy subjects and patients with CF. Patients with CF showed significantly higher levels of salivary chloride, IL-6, IL-8, and TNF-α and lower calcium levels than healthy subjects. Among patients with CF, IL-6 and IL-8 were significantly higher in patients with NTH, while TNF-α was significantly lower in patients with NP. A decreasing trend of TNF-α in patients with severe lung disease was also observed. On the other hand, we did not find significant correlation between cytokine levels and Pseudomonas aeruginosa or Stenotrophomonas maltophilia colonization. These preliminary results suggest that salivary IL-6 and IL-8 levels increase during the acute phase of sinonasal disease (i.e., NTH), while the end stages of pulmonary disease and sinonasal disease (i.e., NP) show decreased TNF-α levels.